(untitled) (Journal of Human Sciences, 2023)
The aim of the current study was to explore religious commitment and its relationship with forgiveness among a sample of couples in the city of Sabha. The study adopted a descriptive-analytical methodology, and the study sample consisted of 84 married couples selected randomly. The study utilized two tools: a religious commitment scale and a forgiveness scale, both of which were developed by the researcher. After ensuring the validity and reliability of the study tools, the following results were obtained: There are differences in the average scores of the sample members, indicating a high level of religious commitment among the study sample, There are statistically significant differences in the forgiveness scale, indicating a high level of forgiveness among the sample members ,There is a positive relationship between religious commitment and forgiveness among the sample, There are significant differences in the forgiveness scale based on age, favoring older individuals, There are no statistically significant differences in religious commitment based on gender, with males and females showing similar levels of commitment, There are statistically significant differences in forgiveness based on gender, with males showing higher levels of forgiveness compared to females, There are no statistically significant differences in religious commitment based on educational level, There are no statistically significant differences in forgiveness based on educational level.